RANK is the intrinsic hematopoietic cell surface receptor that controls osteoclastogenesis and regulation of bone mass and calcium metabolism - Li, Ji (The National Academy of Sciences, 2000)
We have generated RANK (receptor activator of NF-κB) nullizygous mice to determine the molecular genetic interactions between osteoprotegerin, osteoprotegerin ligand, and RANK during bone resorption and remodeling processes. RANK(−/−) mice lack osteoclasts and have a profound defect in bone resorption and remodeling and in the development of the cartilaginous growth plates of endochondral bone. The osteopetrosis observed in these mice can be reversed by transplantation of bone marrow from rag1(−/−) (recombinase activating gene 1) mice, indicating that RANK(−/−) mice have an intrinsic defect in osteoclast function. Calciotropic hormones and proresorptive cytokines that are known to induce bone resorption in mice and human were administered to RANK(−/−) mice without inducing hypercalcemia, although tumor necrosis factor α treatment leads to the rare appearance of osteoclast-like cells near the site of injection. Osteoclastogenesis can be initiated in RANK(−/−) mice by transfer of the RANK cDNA back into hematopoietic precursors, suggesting a means to critically evaluate RANK structural features required for bone resorption. Together these data indicate that RANK is the intrinsic cell surface determinant that mediates osteoprotegerin ligand effects on bone resorption and remodeling as well as the physiological and pathological effects of calciotropic hormones and proresorptive cytokines.